PKM Edukasi dan Konservasi: Pengenalan Ekosistem Mangrove bagi Siswa Sekolah Dasar Berbasis Virtual Reality sebagai Media Pembelajaran Interaktif - Daesusi, Ruspeni; Wahyudi, Dedy; Suher, Suher; Rusdiyanti, Ekita; Solikah, Amanat (Jurnal SOLMA, 2025)
Background: Indonesia, as a coastal country, possesses abundant biological resources, among which the mangrove ecosystem plays a crucial role in maintaining ecological balance, protecting coastlines, and providing habitats for marine life. However, the younger generation’s understanding of the ecological functions of mangroves remains limited, including in Bulak District, Surabaya City. The Community Empowerment Partnership Programme (PKM) on Mangrove Ecosystem Education based on Virtual Reality (VR) was implemented at SD Muhammadiyah 9 Surabaya with the aim of enhancing students’ environmental literacy and improving teachers’ capacity in utilizing digital learning media. Methods: This programme involved socialization, teacher training, VR media implementation, mentoring, and evaluation through student pre-tests and post-tests. Results: The results indicated a significant improvement in students’ understanding of mangrove ecosystems, as reflected by higher post-test scores compared to pre-test scores. Teachers also demonstrated enhanced skills in operating VR media and designing participatory learning activities. Conclusions: Active collaboration among the community service team, schools, and committees contributed to the programme’s success and ensured the sustained use of VR media as an innovative learning strategy. Overall, the integration of VR in environmental education has proven effective, positively impacting students’ ecological literacy, teacher competency development, and sustainable technology-based learning models in coastal areas.